Reducing Tourism Costs and Its Economic Impact on Agriculture: A Dynamic CGE Approach for Kenya - Nobosse Tchoffo, Rodrigue; Derrick Nguepi, Nelson; M. Tafakeu, Marie-Josée; Matsop Dounya, Claude (Eco-Tourism and Sustainable Development, 2025)
Kenya’s economy is predominantly anchored in agriculture and tourism, yet the synergistic potential between these sectors remains underexplored. This study investigates the economic impact of reducing tourism costs on Kenya’s agricultural sector, focusing on productivity, household welfare, and labour market dynamics. Employing a dynamic Computable General Equilibrium (CGE) model calibrated with 2019 data, we simulate a 10% reduction in tourism costs. Our findings reveal significant positive spillover effects on agriculture, with key metrics showing a 1.32% increase in intermediate consumption and a 1.66% rise in domestic demand for agricultural products by 2030. These gains translate into substantial welfare improvements, particularly for rural households, and contribute to enhanced food security, aligning with SDG 2 (Zero Hunger). The policy also stimulates broader economic growth (SDG 8), evidenced by a steady rise in GDP. However, the benefits are tempered by persistent gendered disparities, as female-headed households experience lower gains in income and employment. The study underscores the importance of strengthening sustainable tourism-agriculture linkages (SDG 12) as a strategy for inclusive development. We conclude that while reducing tourism costs is a potent catalyst for economic growth, its long-term sustainability requires careful design to ensure the financial viability of tourism operators and government revenue. It must be integrated with targeted gender-responsive interventions and strategies to build resilient cross-sectoral value chains to ensure equitable distribution of benefits and fully realise the sustainable development potential of this intersectoral relationship.